Numerical Simulation of the Influence of Vent Conditions on Hydrogen Flame Propagation. Issue 13 (3rd October 2021) - Zhou, Ning; Mei, Yuan; Li, Xue; Chen, Bing; Huang, Wei-Qiu; Rasouli, Vamegh; Zhao, Hui-Jun; Yuan, Xiong-Jun
ABSTRACT: In order to reduce the damage caused by a gas explosion in a ventilation duct, a Large Eddy Simulation (LES) model was used to simulate the hydrogen/air explosion process in the ventilation duct under different side vent. The results show that in the process of flame propagation, the large size side vent near the ignition end produces a larger discharge effect, which causes more serious distortion and longer time for the flame front passing through the side vents. The influence mechanism of the side vent on the flame propagation is different at different stages of flame propagation. When the flame front is behind the side vent, the positive flow field traction on the flame front increases the contact area between the flame front and unburned gas, and thus accelerates the flame propagation. When the side vent is 1 m away from the ignition end, with the side vent diameter increasing from 40 mm to 80 mm, the peak flame propagation speed increases by 19.02% before the flame reaches the vent. When the flame front passes through the side vent, the exhaust of the side vent and the disturbance of the vertical flow field can restrain the flame propagation. However, when the flame front is in front of the vent, the synergistic effect between turbulent vortex and reverse flow field causes the flame propagation speed to fluctuate greatly. The influence of the side vent size on the explosion relief effect is restricted by the side vent position. When the side vent is located in the pressure rising section, the pressure relief effect of the side vents with different sizes is very great and is almost unaffected by the size of the side vent. When the side vent is 1 m away from the ignition end, the peak overpressure in the tube decreased by 50.75%, 52.88% and 55.43%, respectively, when the diameter of the side vent was 40 mm, 60 mm and 80 mm. On the contrary, when the side vent is outside the pressure rising section, the pressure relief effect of the side vent will be weakened, and vents with different sizes have a great alteration to pressure relief effect. For the side vent being 5 m from the ignition end, the peak overpressure in the tube decreased by 4.49%, 13.41%, and 35.51%, respectively, when the diameter of the side vent was 40 mm, 60 mm, and 80 mm.